Inside Cover: Cancer Cell Imaging Using in Situ Generated Gold Nanoclusters (ChemPhysChem 1/2016). Issue 1 (January 2016) - Chattoraj, Shyamtanu; Amin, Md. Asif; Mohapatra, Saswat; Ghosh, Surajit; Bhattacharyya, Kankan
Abstract : High glutathione levels in a cancer cell facilitate the formation of fluorescent gold nanoclusters in situ with very little fluorescence from noncancer cells. Such selective and specific imaging of cancer cells may have implications in cancer detection and therapy. More information can be found in the Full Paper by S. Ghosh, K. Bhattacharyya et al. onpage 61 in Issue 1, 2016 (DOI:10.1002/cphc.201500731 ).